2014
DOI: 10.1002/jbm.a.35103
|View full text |Cite
|
Sign up to set email alerts
|

The preparation and comparison of decellularized nerve scaffold of tissue engineering

Abstract: To integrate tissue engineering concepts into strategies to repair spinal cord injury (SCI) has been a hotspot in recent years, and the choice of scaffolding material is crucial to tissue engineering. Recently, decellularized nerve scaffold becomes a central concern due to its peculiar superiority. In this study, the decellularized nerve scaffold was prepared with three different methods and a comparison was made to acquire an ideal scaffold materials. All sciatic nerves from Sprague-Dawley (SD) rats were rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…Freeze/thaw [117,120,132,154] Not required for complete decellularization May be useful for tissue storage Effects of freeze/thaw vs. fresh have not been examined SDS [116,118,119,115,120,121,132,155,156] Improves removal of cytoplasmic and nuclear material Effective for cellular removal when used alone Concentration and exposure time vary widely among protocols and for different source animals More detrimental to mechanical properties than other detergents Residual SDS is harmful Triton X-100 [116,118,115,117,120,121,132,[154][155][156] Only effective for cellular removal when used in conjunction with other agents Concentration and exposure time vary widely among protocols Effective for removal of residual SDS Sodium deoxycholate [118,132] Not sufficient for cellular removal when used without additional decellularization agents Ionic detergents damage matrix components Trypsin [118,117] Only effective for cellular removal when used in conjunction with other agents…”
Section: Method/agent Results Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Freeze/thaw [117,120,132,154] Not required for complete decellularization May be useful for tissue storage Effects of freeze/thaw vs. fresh have not been examined SDS [116,118,119,115,120,121,132,155,156] Improves removal of cytoplasmic and nuclear material Effective for cellular removal when used alone Concentration and exposure time vary widely among protocols and for different source animals More detrimental to mechanical properties than other detergents Residual SDS is harmful Triton X-100 [116,118,115,117,120,121,132,[154][155][156] Only effective for cellular removal when used in conjunction with other agents Concentration and exposure time vary widely among protocols Effective for removal of residual SDS Sodium deoxycholate [118,132] Not sufficient for cellular removal when used without additional decellularization agents Ionic detergents damage matrix components Trypsin [118,117] Only effective for cellular removal when used in conjunction with other agents…”
Section: Method/agent Results Considerationsmentioning
confidence: 99%
“…Ionic detergents are used in each of 131 the published protocols. Bhrany et al [39] used an SDS-based solu- 132 tion while Marzaro et al [24], Ozeki et al [40], Totonelli et al [41], 133 and Keane et al [23] used a 4% sodium deoxycholate solution as 134 the main decellularization agent. Each of the protocols also 135 required an endonuclease (DNase and/or RNase) to remove resid- 136 ual nucleic acids.…”
mentioning
confidence: 97%
“…In terms of nerve decellularization, nuclease was applied with other methods because of its limited cell removal ability (Kim et al, ). Wang et al () reported that a combination of freezing–thawing and nulease is better than detergent alone or a combination of a nonionic agent (Triton X‐100) and nuclease method for cell removal. However, their evaluations only consisted of H&E staining and electron microscopic examinations.…”
Section: Discussionmentioning
confidence: 99%
“…These agents destroy specific target structures at the molecular level, which facilitates their removal from the tissue. In particular, nucleases such as DNase and RNase could fragment nucleic acid sequences by hydrolysing their phosphodiester bonds and produce good decellularization results when used in combination with chemical agents (Crapo et al, ; Grauss, Hazekamp, van Vliet, Gittenberger‐de Groot, & DeRuiter, ; Wang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, not all studies specify the exact scoring system that was used or only report the presence or absence of components F I G U R E 1 Overview of the different staining methods and example of scores 1-5. One resembles severe structural damage or absence of the component and five resembles a "perfect" structure similar to the native and unprocessed nerve which makes it difficult for the reader to appreciate the results and impossible to compare outcomes (Ma et al, 2011;Wang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%